Reproductive cycle and sexual size dimorphism of the Nile Crocodile (Crocodylus niloticus) in the Okavango Delta, Botswana - Detoeuf-Boulade, Audrey Simone (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2006.